A process model of entrepreneurial venture creation - Bhave, Mahesh P. (Journal of Business Venturing, 1994)
The process model of entrepreneurial venture creation developed in this paper is based on interviews with entrepreneurs who started twenty-seven business in a range of industries in upstate New York. The venture creation process described here is an iterative, nonlinear, feedback-driven, conceptual, and physical process. The model includes internally and externally stimulated opportunity recognition, commitment to physical creation, set-up of production technology, organization creation, product creation, linking with markets, and customer feedback. For analytical convenience, the process has been divided into the opportunity stage, the technology set-up and organization-creation stage, and the exchange stage. Business concept, production technology, and product are respectively the core variables representing the three stages. Entrepreneurs introduce differing amounts of novelty at each core variable during venture creation, and the varying amounts of novelty qualitatively distinguish one kind of entrepreneurship from another. For the researcher, the model suggests a better method for specifying samples of entrepreneurial firms. It shows how studies on the context of venture creation can be more specific, and proposes that novelty at the core variables be operationalized as a step toward defining the entrepreneurial content of ventures. For the prospective entrepreneur, the model will serve as a useful road map. It will alert the entrepreneur to the strategic issues at each stage in the venture creation process, particularly when introducing significant novelty at any of the core variables.